Barriers influencing intention towards practicing urban agriculture - Mohd Johari, Abdullah Asahari (2018)
Agricultural activity among the residents living in the city for the purpose of producing food itself is a practical approach and reduces daily spending due to the rising cost of living in the city. Based on the situation, there is effort to implement urban agriculture that aims to encourage urban dwellers to plant their own vegetables / crops around their homes so that the burden of rising cost of living can be reduced. The purpose of this study is to determine whether a person's barriers to urban farming activities. Samples of 400 respondents were randomly selected in the Klang Valley. Quantitative data was collected through surveys and analyzed using descriptive analysis and analysis factors. The analysis shows that the majority of them assuming that knowledge is very important to make urban agriculture activities. Knowledge is needed because it is the starting point in urban agriculture. Land and cost are also said to be a barrier for someone to do or start urban agricultural activities. This is evidenced by the results of the factors analysis that have been made and find that knowledge, land and cost are the barrier that are still relevant today.